Field Measurements of Free Ascending Behavior of Occupants along Medium-Long Stairway - Junmei Li; Zhao Qi; Yanfeng Li; Wan-Ki Chow; Fei Xie; Qiwei Dong (Applied Sciences, 2022)
The human behavior of walking upstairs was studied by field measurement in a 10-storey building, which simulates the greatest depth of most underground facilities. The effects of age, gender, walking distance, and fatigue on individual free ascending speed on stairs were investigated. The experimental results showed that walking distance and fatigue due to the long-distance upward walking have great impact on the upward walking and ascent speed. When climbing over 8 floors (vertical height about 30 m), the mean ascent speeds were 0.97 m/s and 0.78 m/s for young males and females, and 0.91 m/s and 0.68 m/s for middle-aged males and females, respectively. The mean ascending speed that is used to predict the evacuation time should be combined with the traveling distance or floor levels. Ascent speed models for males and females walking along a medium-long stairway were developed to describe the fatigue effect on ascending speed based on the vertical heights travelled.